IMPLEMENTASI METODE ROLE-PLAYING SEBAGAI INOVASI DALAM PEMBELAJARAN FIQIH MUNAKAHAT UNTUK MENINGKATKAN PARTISIPASI DAN PEMAHAMAN SISWA - M Mahbubi; Ayu Widiawati (LPPM STAI Muhammadiyah Probolinggo, 2025)
The learning of Fiqh Munakahat in Islamic educational institutions often faces challenges, particularly in terms of student engagement and understanding. Conventional teaching methods, which tend to be theoretical and less interactive, often result in low participation and limited conceptual understanding among students. This study aims to examine the effectiveness of role-playing as an innovative strategy to improve student participation and understanding in Fiqh Munakahat learning. The research approach used is a quasi-experimental design with a mixed-methods approach at Madrasah Diniyah Muadalah Aliyah (MDMA) Nurul Qarnain, Sukowono, Jember. The study subjects consisted of 40 eleventh-grade students, divided into experimental and control groups. Data were collected through pre-tests and post-tests to measure student understanding, as well as observations and interviews to assess the level of participation in the learning process. The results of the study showed a significant improvement in student understanding after the implementation of the role-playing method, confirmed through statistical analysis of the pre-test and post-test. Additionally, observations revealed that this method encouraged active student involvement, increased motivation, and deepened their understanding of Fiqh Munakahat concepts through role simulations. These findings suggest that the role-playing method is an effective and innovative teaching strategy in Fiqh Munakahat education. The implications of this study indicate that using more interactive teaching methods could serve as an alternative for educators to enhance the quality of learning in Islamic educational institutions.